A-104 Examining Methods of Executive Ability from Trail Making Test Part B in Retired Football Players. (30th August 2021) - Lopez-Hernandez, Daniel W; Nordberg, Bethany A; Bueno, Alexis; Litvin, Pavel Y; Bichlmeier, Amy; Smith, Kristina E; Olmos, Winter; Sidhu, Jasman; Saravia, Sarah; Mangassarian, Selina; Fatoorechi, Sarah; Hardy, David; et al.
Abstract: Introduction: Repeated sports-related concussions have been associated with cognitive deficits, similar to other forms of traumatic brain injury. We investigated three different measures of executive ability derived from the Trail Making Test part B (TMT-B) in healthy comparison (HC) adults and retired football players. Methods: The sample consisted of 32 HC, 15 retired football speed players (FSP; e.g., quarterbacks), and 53 retired football non-speed players (FNP) participants. Participants were administered both TMT part A (TMT-A) and TMT-B, and total time for completion was recorded. A series of ANCOVAs, controlling for age and education were conducted to evaluate group differences in executive abilities. Executive measures included the TMT-B raw score (i.e., seconds to complete TMT-B), the raw score difference (in seconds) between TMT-A and TMT-B (TMT-BA), and the difference between a predicted TMT-B score (TMT-BP) and the obtained TMT-B score (TMT-BBP). Correlations between TMT-B, TMT-BA, and TMT-BBP and other executive functioning tests (i.e., letter fluency and animal naming) were evaluated. Results: Results revealed that the HC group outperformed both retired football player groups on all measures of executive ability derived from TMT-B, p's < 0.05, ηps2 = 0.18–0.45. Furthermore, the retired FNP TMT-B and TMT-BA were significantly correlated with both letter fluency and animal naming, r's = −0.40 to −0.36, p's < 0.05. Discussion: We found that the HC group outperformed both retired football player groups on all three TMT variables. In our retired FNP sample, more TMT variables correlated with executive functioning measures which suggests that TMT-B and TMT-BA are likely better measures of executive ability than TMT-BBP.